Pembekalan Mahasiswa di STAK PESAT Salatiga Bertajuk “Mengenali dan Mengelola Emosi” - Debora Tiurlan Tambunan (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Adolescence, the period currently being experienced by college students, is the most important and dynamic period in the development of human emotions. Individuals who have emotional intelligence are individuals who can adapt in various situations and are able to establish good relationships with other humans. Realizing the importance of this, an education program entitled